TINGKAT PENGETAHUAN KADER TENTANG PEMANTAUN TUMBUH KEMBANG BALITA PADA KONDISI DARURAT - Nurulfuadi, Nurulfuadi (Jurnal Dedikatif Kesehatan Masyarakat, 2025)
Prevalence stunted among toddlers in Palu City in 2022 is 24.7%, wasted at 12.8%, and underweight at 24.7%, and overweight at 1.9%. Child growth and development problems, including the decline in post-disaster nutritional status in Palu City which has increased compared before the disaster. This can be caused by lack of access to health services and inadequate health personnel. Therefore, training to monitor the growth and development of toddlers in emergency conditions needs to be carried out. The aim of this study is to increase the knowledge of cadres as one of the health workers in the smallest unit, namely the posyandu in Duyu Village, Tatanga District, Palu City regarding monitoring the growth and development of toddlers during emergency conditions. The partner in this study is the Head of Duyu Village, Palu City. The methods used are lectures and direct practice. The results showed that the training had a positive influence on increasing cadres' knowledge about monitoring the growth and development of toddlers in emergency conditions. This study is an effort to increase the positive aspects of cadre knowledge.